Women's Patchwork Dresses with Mixed Media Techniques in the Creation of Painting - Johari, Adawiah Rizqi; Tarenaksa, Babat Nufus; Maharoni G, Lalu Aswandi (JUPE : Jurnal Pendidikan Mandala, 2024)
The purpose of this final project entitled "Women's Patchwork Dresses with Mixed Media Techniques in the Creation of Painting" is to visualize several forms of women's dresses in the form of Mixed Media works between patchwork and acrylic paint, the art idea of visualizing female figures as subject matter depicting dresses or women's clothing with sewing techniques, with the aim of achieving the author's goal of utilizing patchwork waste as a work of art. with the embodiment process, namely; 1). Sketch, is the process of designing a rough image or initial process, 2). Preparation of tools and materials, is the initial process before making work, 3). The stringing process is a process that visualizes the selected fabrics onto the background cloth, 4). Giving color to the sketch that has been made, 5). Final Process, is the final stage in making a work that can be considered as a finishing process, resulting in works with mixed media techniques between patchwork and acrylic paint depicting princesses or female figures in different dresses that reflect their respective characters. the work made by the author with the concept of utilizing patchwork waste is very basic in nature where a work will require accountability and in-depth explanation of the work of art. All works use the Robe de Style dress style which was popularized in the 1920s as an alternative to the chemise dress. Obstacles when preparing the type and color of cloth and painting the female figure, but by applying balance, domination, and proportion, the author succeeded in visualizing it in the form of a female figure.